POST OCCUPANCY EVALUATION (POE) FOR ENHANCING SATISFACTION LEVEL OF COMFORTS IN MALAYSIA’S SCHOOL BUILDINGS (Journal of Technology and Operations Management, 2023)
The physical factors of building performance in a school building must be determined to meet the users’ basic requirement of comfort level. The disruption of physical factors such as ventilation, lighting, or thermal may constitute to reduce the productivity and efficiency among users. Thus, Post Occupancy Evaluation (POE) is a significant tool to indicate the level of satisfaction and occupants’ comfort in ensuring the current issues mainly related to physical aspects such as indoor environmental quality, space utilization, energy efficiency, and so forth. Therefore, the primary purpose of this study is to assess the satisfaction level of school building users in Malaysia, including students, teachers, and staff to improve the quality of the indoor environment in a school building as the leading learning space for the future generation. The interview was conducted with 12 participants in determining the satisfaction level of building performance assessment on school buildings. Next, the survey instrument was distributed to 224 respondents in 7 different schools, to evaluate the awareness level of POE in current practice and to analyse the physical criteria to conduct the evaluation standards on school buildings in Malaysia. This study concludes that POE is the most accurate approach to estimate the quality of building performance, especially for school buildings. Also, it should be emphasized as a continuous routine of physical environment evaluation or a periodic assessment of school buildings.